Beneficial effects of short-term breastfeeding versus non-breastfeeding in early life against childhood obesity: findings from the US-based population study NHANES - Menglin Zhou; Luyao Hu; Fan Li; Jie Wen; Zhaoxia Liang; Danqing Chen (BMC, 2024)
Abstract Background Breastfeeding is widely recognized for its potential to reduce childhood obesity. However, research investigating these benefits in children breastfed for a short duration (up to 6 months) remains limited despite this being a common practice globally. Methods This study focused on a population breastfed for 6 months or less to determine the potential benefits of short-term breastfeeding for preventing childhood obesity. Data were collected from five survey cycles of an US-based population study (the National Health and Nutrition Examination Survey (NHANES)), spanning 2009-2020. A sample of 3,211 children aged 2-6 years was selected, including 1,373 never breastfed and 1,838 ever breastfed. Logistic regression analysis examined the direct association between short-term breastfeeding and childhood obesity. Subsequent subgroup analyses were conducted. Additionally, stratified logistic regression explored the relationship between childhood obesity and the introduction of other early nutrition in both ever-breastfed and never-breastfed children. Results Overall, breastfeeding for 6 months or less did not directly prevent childhood obesity. However, among participants with older mothers (aged 35 or above), short-term breastfeeding was associated with a lower risk of childhood obesity compared to never being breastfed (OR 0.31, 95% CI: 0.17, 0.59). Similarly, children aged 3-4 years who were breastfed for > 3 ~ 6 months exhibited a lower obesity risk (OR 0.56, 95% CI: 0.35, 0.89). In ever-breastfed children, delayed infant formula introduction was linked to a lower risk of obesity (P-trend < 0.05: introduction at age ≤ 1 vs. >1 ~ 3 vs. >3 months). Conversely, for non-breastfed children, introducing milk (other than breast milk or formula) later (≥ 12 versus < 12 months) and introducing alternatives to whole cow's milk were associated with lower obesity risks (OR 0.54, 95% CI: 0.37, 0.78; OR 0.21, 95% CI: 0.08, 0.60, respectively). Notably, these trends were not observed in ever-breastfed children. Conclusions Short-term breastfeeding may offer some benefits in preventing childhood obesity for specific populations. Additionally, it could potentially mitigate risks associated with the introduction of formula and cow's milk at inappropriate times.